Use of type VII collagen gene (COL7A1) markers in prenatal diagnosis of recessive dystrophic epidermolysis bullosa. Issue 9 (September 1995) - Dunnill, M G; Rodeck, C H; Richards, A J; Atherton, D; Lake, B D; Petrou, M; Eady, R A; Pope, F M
Abstract : Generalised recessive dystrophic epidermolysis bullosa (EB) is a severe inherited disease in which patients suffer from blistering and scarring of the skin and mucous membranes after minor mechanical trauma. Tight genetic linkage has been established to the type VII collagen gene (COL7A1) at 3p21, with no evidence of locus heterogeneity. Several COL7A1 mutations have now been identified in recessive dystrophic EB patients. Prenatal diagnosis has been performed by examination of a fetal skin biopsy taken at about 16 weeks' gestation, and relies on identification of characteristic ultrastructural and immunohistochemical changes. We have now achieved a first trimester prenatal diagnosis using intragenic and flanking COL7A1 markers in a pregnancy at risk for recessive dystrophic EB. Segregation of the informative markers predicted the baby would be an unaffected carrier. The pregnancy continued to term and a healthy baby was born, confirming this result.